2004
DOI: 10.1021/ja0390348
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Mesoporous Metal Oxides Using Nano-Propping Hybrid Gemini Surfactants

Abstract: Noble Gemini surfactants containing a siloxane moiety have been designed and successfully synthesized in the present study and are utilized as structure-directing agents for mesoporous metal oxides such as zirconia, titania, and vanadia. The siloxane moiety is believed to play an important nano-propping role during the surfactant removal by direct calcination, yielding thermally stable mesoporous metal oxides. It is also believed that the synthesis strategy described here can be applied to the synthesis of rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 11 publications
1
54
0
Order By: Relevance
“…6. Other hollow par ticles prepared by sur factants vesicles templates method include hollow CaCO 3 78) , hollow zirconium oxide (ZrO 2 ) 79) , hollow PS 80) , and hollow aluminosilicate 81) .…”
Section: Surfactant Vesicle Template Methodsmentioning
confidence: 99%
“…6. Other hollow par ticles prepared by sur factants vesicles templates method include hollow CaCO 3 78) , hollow zirconium oxide (ZrO 2 ) 79) , hollow PS 80) , and hollow aluminosilicate 81) .…”
Section: Surfactant Vesicle Template Methodsmentioning
confidence: 99%
“…One of the main disadvantages of use of ionic templates is the need for extreme pH values for synthesis and a limited lower pore size. Synthesis of highly stable Zr, Ti, and V oxides with Gemini templates are described by Kim [76,77] which contain many hydrophilic or hydrophobie groups and form micelles at low concentrations. Synthesis of porous transition metal oxides by neutral method, based on the use of di-or tri-block copolymers is characterized by simplicity, low cost, and high tolerance to a large number of elements [78][79][80].…”
Section: Template-assisted Synthesismentioning
confidence: 99%
“…In order to preserve nanostructured natures of materials at elevated temperatures, retardation of sintering behaviors was considered. However, only few reports emphasized stabilization of the nanostructured materials at high temperatures [1][2][3][4][5]. Pang et al showed the size of SnO 2 nanoparticles could be controlled as small as 3.5 nm even heat treatment at 600°C [3].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al found that surface-modified methylsiloxyl groups on the metal oxide gel could prevent grain growth of metal oxides during high temperature treatments and excellent gas sensing properties were shown [4]. Lyu et al also showed that the thermal stabilities of mesoporous metal oxides were improved by introducing silicon-contained hybrid Gemini surfactants as a nano-propping agent [5].…”
Section: Introductionmentioning
confidence: 99%